THE EFFECT OF ACCOUNTING KNOWLEDGE, BUSINESS STRATEGY AND WORK MOTIVATION ON THE QUALITY OF MANAGEMENT ACCOUNTING INFORMATION SYSTEMS : (Survey of Retail Store Management Employees at Palembang Square Mall) - Tampubolon, Enggal Marito Yuliarti; Hertati, Lesi; Sari, Rafika (Transpublika Publisher, 2023)
This study aims to analyze and describe the effects of Accounting Knowledge, Business Strategy, and Work Motivation on the Quality of Management Accounting Information Systems for retail store employees at Palembang Square Mall, Palembang City. The sampling technique used is simple random sampling. The data analysis technique employed in this research is multiple linear regression analysis, processed using the SPSS software application version 26.0. The data for this research consists of 38 respondents, obtained from retail store employees in Palembang Square Mall, Palembang City. The findings of this research indicate that Accounting Knowledge, Business Strategy, and Work Motivation have a positive and significant effect on the Management Accounting Information Systems and the utilization of Management Accounting Information Systems. All three factors (Accounting Knowledge, Business Strategy, and Work Motivation) exhibit positive and significant effects on the Management Accounting Information System, either partially or simultaneously.